2018
DOI: 10.1080/01459740.2018.1482548
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Injury, Supervision, and Discourses on Childproofing Devices

Abstract: Unintentional injury prevention research focuses on parental supervision as critical to reducing toddler injury. We examine how the promotion of childproofing-as a mode of supervision-sells mothers "peace of mind" while also increasing "intensive mothering" and the "privatization of risk." Drawing on the childproofing literature and meaning centered interviews with mothers of toddlers and childproofing business owners, we argue that the connection made by these groups between childproofing and "good parenting"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
1
0
3
Order By: Relevance
“…Due to their inherent curiosity and natural tendency to place objects in their mouths, children at this age are at an especially high risk of medicinal drug poisoning 27 . The enforcement of child‐resistant packaging regulations was found to reduce child mortality from the unintentional ingestion of oral prescription drugs 28 . In addition, adherence to the prescribed drug regimen is important, especially in children, as studies revealed differences in the absorption, distribution, metabolism, and excretion of drugs in children, which make them more vulnerable to drug toxicities 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Due to their inherent curiosity and natural tendency to place objects in their mouths, children at this age are at an especially high risk of medicinal drug poisoning 27 . The enforcement of child‐resistant packaging regulations was found to reduce child mortality from the unintentional ingestion of oral prescription drugs 28 . In addition, adherence to the prescribed drug regimen is important, especially in children, as studies revealed differences in the absorption, distribution, metabolism, and excretion of drugs in children, which make them more vulnerable to drug toxicities 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Outra ação preventiva relacionada à atuação dos professores foi no cuidado com brinquedos e objetos quebrados, pontiagudos ou pequenos, reforçando a importância de se utilizar dispositivos mais seguros para as crianças. Estudos como esse podem fortalecer a relevância em realizar mudanças na fabricação de brinquedos e materiais mais seguros destinados ao uso de crianças (Dao, 2018). Pesquisa realizada em Tocantins descreve algumas ações preventivas relacionadas à atuação do professor, como a substituição dos brinquedos que oferecem riscos, utilização de protetores nas tomadas e realização de orientações para todos os responsáveis nos cuidados com as crianças, com a finalidade de promover um ambiente escolar mais seguro para o aprendizado (Bonilla-Escobar & Gutiérrez, 2014).…”
Section: Discussionunclassified
“…Quanto às ações referidas pelos professores relacionadas à estrutura física/ mobília do CMEI, a modificação do ambiente ainda é considerada uma das estratégias primárias para a prevenção dos acidentes não-intencionais (Dao, 2018). Vale salientar a importância de propostas para a implementação de políticas com o objetivo de transformar o ambiente mais seguro para favorecer, e não substituir, o ato de supervisionar a criança (Brasil, 2006).…”
Section: Discussionunclassified
See 1 more Smart Citation